Habitat variation effects on cavity-nesting bee fitness, community assemblages, and parasite interactions in the Colorado Front Range - Dodge, Jessie M., author; Davis, Thomas S., advisor; Galbraith, Sara M., committee member; Paschke, Mark, committee member; Stewart, Jane E., committee member (Colorado State University. Libraries, 2024)
Although many dry forested ecosystems in the western US are shaped by disturbances like wildfire and forest management treatments, little is known about their effects on native solitary bee fitness. This is an important knowledge gap, as most bees in the western US are solitary and are crucial for pollination in forested ecosystems. Therefore, I test how wildfire and forest management treatments affect cavity-nesting solitary bee fitness traits including diet breadth and quality, provisioning ability, reproduction and brood development, parasite abundance, and community network metrics. This was done by deploying artificial nesting boxes in the ponderosa pine forest of Boulder County, CO that either burned at higher severity, thinned by hand, or were unburned and untreated control. For my first two chapters, I used the solitary bee, Osmia lignaria as a model species to evaluate bee fitness responses to variations in forest structure, floral density, and climatic conditions. I found that O. lignaria foraged for pollen from specific flora, regardless of on-site presence, which was affected by climate and forest structure, but effects varied from year to year. Otherwise, habitat variation did not affect O. lignaria nest provisioning, reproduction, or development. However, the abundance of their kleptoparasite, Tricrania stansburyi, decreased with increased wildland urban development. Finally, in my last chapter, I utilized artificial nest boxes to collect local cavity-nesting bees and wasps to compare differences in community composition, host-parasite interactions, and emergence rates among Burned, Control, or Treated sites. The solitary bee, Osmia calla was found to be the most abundant species, indicative of burned sites whereas the kleptoparasite, Nemognatha sparsa, and parasitoid, Monodontomerus spp., were the most abundant parasites found within all habitat types. Control sites were found to have the most host-parasite interactions, with parasites exhibiting more generalist relationships with hosts, followed by treated sites, with burned sites having the most specialized host-parasite interactions. Collectively, my results demonstrate that disturbance-caused habitat variations had little effect on the fitness of the solitary bee, O. lignaria, despite affecting their access to nutritional opportunities, suggesting they can reproduce within various dry, mixed conifer forested habitats. However, urbanization in forested ecosystems likely decreases exposure to nest parasites. Alternatively, local, cavity-nesting bee-parasite interactions differed among habitat types, with hosts inhabiting control sites portraying more parasitic pressure. Thus, some cavity-nesting bee species may be more influenced by habitat variations than O. lignaria, and this is likely mediated by interactions with parasitic species. The interacting effects of disturbances and parasite pressure on bee fitness found here can be used to inform native bee conservation strategies. For one, floral surveys may not reflect floral species bees are using for foraging so alternative methods investigating pollen sources bees are using for forage are suggested. Secondly, the loss of natural habitat with increasing urbanization within forested habitats can decrease kleptoparasite abundance but provide early season solitary bees with additional foraging sources. Finally, cavity-nesting bees and wasps in unburned and untreated habitats demonstrate higher parasitic pressure than burned and treated habitats, suggesting habitat variations caused by these disturbances may relieve parasitic pressure. Overall, monitoring bee parasite abundance may indicate healthy pollinator habitats within the forests of the Colorado Front Range.
Keywords: forest restoration; pollen quality; wildfire; phenology; diet breadth; reproduction